Transfer of Property Rights Over KPR House by Debtor to a Third Party Before the Installment is Paid Off - Firsty Oxana Dayinta Talia; Indri Fogar Susilowati (NOVUM : JURNAL HUKUM, 2024)
One of the Indonesian government's programs to fulfill the housing needs of Low-Income Communities (MBR) is through the Home Ownership Credit (KPR) program, implemented via a credit agreement between PT Bank Tabungan Negara (Persero) Tbk. and the customer. A legal issue arises when the debtor transfers the KPR house to a third party without the written consent of the creditor while the mortgage is still under installment. This study aims to analyze whether such a transfer of ownership rights is legally permissible and to examine the legal consequences of this action. The research employs normative legal methods with statutory, conceptual, and case approaches, using a prescriptive analysis technique. The findings show that the transfer of ownership rights to KPR houses during the installment period without creditor approval violates the provisions of the credit agreement and the Mortgage Law. This action also contravenes the fiduciary principle embedded in the credit system, where the creditor retains legal control over the asset until the debt is fully repaid. The legal consequence is the absence of legal certainty for the third-party buyer, as the transfer cannot be registered at the Land Office, thus rendering the transaction invalid in the eyes of the law. The study recommends increasing public awareness of credit agreement obligations and stricter enforcement from financial institutions to prevent unauthorized transfers and protect all parties involved.